Pengembangan Media Pembelajaran Inovatif Berbasis Audio Visual Pada Mata Kuliah Aljabar Linear - Zahara, Yulia; Fitri Ayu Ningtiyas; Nurul Afni Sinaga; Rifaatul Mahmuzah (FKIP Universitas Mataram, 2024)
The need for learning media that supports learning outcomes and can increase student motivation in the learning process, so that the development of learning videos becomes an alternative because it helps students to understand the concepts of the material presented. This research aims to test the validity, effectiveness, and practicality of the developed learning media. This type of research is called research and development. The method used is Borg and Gall, which have been modified. However, in this study, this research is limited to the development stage. The validity of the media is assessed through a questionnaire given to 4 experts, 2 media experts and 2 material experts. Based on the validation results by media experts and material experts, ratings of 82% and 80% were obtained respectively. Therefore, the learning video is declared valid. Based on the test results of 83 students, it was found that 78.31% of students achieved a minimum grade of B with effective criteria. Furthermore, based on the practicality test from the student response questionnaire, a score of 83.43% was obtained. This means that the learning media is valid and practical to use. Thus, this learning media can be declared valid, effective, and practical, and it has benefits in supporting the linear algebra course. Therefore, this media can support the learning process in class becomes more enjoyable.